Clinical Differences between Eosinophilic and Noneosinophilic Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Multicenter Cross-Sectional Study. (12th November 2020) - Dai, Guangming; Ran, Yajuan; Wang, Jiajia; Chen, Xingru; Peng, Junnan; Li, Xinglong; Deng, Huojin; Xiao, Min; Zhu, Tao
Abstract : Rationale . Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is highly heterogeneous with a plethora of different etiologic factors and inflammatory presentations. COPD with higher blood eosinophil count is associated with increased readmission rates and better corticosteroid responses. However, the clinical features of eosinophilic AECOPD are not well explored. Thus, this study was aimed at exploring the clinical differences between eosinophilic and noneosinophilic AECOPD. Methods . A total of 643 AECOPD patients were enrolled in this multicenter cross-sectional study. Finally, 455 were included, 214 in the normal-eosinophil AECOPD (NEOS-AECOPD) group, 63 in the mild increased-eosinophil AECOPD (MEOS-AECOPD) group, and 138 in the severe increased-eosinophil AECOPD (SEOS-AECOPD) group. Demographic data, underlying diseases, symptoms, and laboratory findings were collected. Multiple logistic regression analysis was performed to identify the independent factors associated with blood eosinophils (EOS). Correlations between blood EOS and its associated independent factors were evaluated. Results . The significant differences in 19 factors, including underlying diseases, clinical symptoms, and laboratory parameters, were identified by univariate analysis. Subsequently, multiple logistic regression analysis revealed that lymphocyte%, neutrophil% (NS%), procalcitonin (PCT), and anion gap (AG) were independently associated with blood EOS in AECOPD. Both blood EOS counts and EOS% were significantly correlated with lymphocyte%, NS%, PCT, and AG. Conclusions . Collectively, blood EOS was independently associated with lymphocyte%, NS%, PCT, and AG in AECOPD patients. Lymphocyte% was lower, and NS%, PCT, and AG were higher in eosinophilic AECOPD. Our results indicate that viral-dominant infections are the probable major etiologies of eosinophilic AECOPD. Noneosinophilic AECOPD is more likely associated with bacterial-dominant infections. The systemic inflammation in noneosinophilic AECOPD was more severe.